دور البنك المركزي في الرقابة على القطاع المصرفي الجزائري - ميم, رشيدة; ليفة, جهيدة; مجيدي, صبرينة; خياري, جهاد الاسلام (University of eloued جامعة الوادي, 2018)
Our study facuses on the main role of the central bank in the conrol of the mani tariol sector in which we control different commercial bamks stricthy to insure the stability of the last . Within this study we will define various mecha mims used in each bank in algaria inaddihim to emsuning regulath ons there fore analysis chould be applied to realize the legal envinment .
مذكرة ماستر نقدي وبنكي
Keywords: البنك المركزي، النظام المصرفي ، الرقابة الاشرافية; Central bank, mom tanial system, stability system,sur vey control